2013
DOI: 10.1007/s00198-013-2378-6
|View full text |Cite
|
Sign up to set email alerts
|

Additive association of vitamin D insufficiency and sarcopenia with low femoral bone mineral density in noninstitutionalized elderly population: the Korea National Health and Nutrition Examination Surveys 2009–2010

Abstract: These data showed that an association between vitamin D insufficiency and low BMD was more prominent in elderly subjects with sarcopenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 42 publications
2
25
0
1
Order By: Relevance
“…Lee et al [29] did a study with a cohort of elderly participants in two Korean national surveys, having selected 1596 males and 1886 females older than 60 years. DXA was used to assess appendicular skeletal muscle mass (SMM) and BMD.…”
Section: Resultsmentioning
confidence: 99%
“…Lee et al [29] did a study with a cohort of elderly participants in two Korean national surveys, having selected 1596 males and 1886 females older than 60 years. DXA was used to assess appendicular skeletal muscle mass (SMM) and BMD.…”
Section: Resultsmentioning
confidence: 99%
“…Regrettably, the Western-type diet provides more than 10 times higher levels of n-6 compared to n-3 PUFA, enabling an environment conducive to LGCI, obesity and other adverse chronic conditions. Therefore, the recommendations are geared toward lowering the n-6/n-3 ratio by reducing n-6 and increasing n-3 PUFA consumption, although it might be difficult to maintain the precise ratio between the two (Office of Dietary Supplements website, available at: http://ods.od.nih.gov/ factsheets/Omega3FattyAcidsandHealth-HealthProfessi onal/#disc; Kelly et al 2013, Kim et al 2013, Ilich et al 2014a). …”
Section: Changes In Dietary Intake and Nutrient Requirements With Agingmentioning
confidence: 99%
“…Regarding the muscle, inadequate vitamin D has recently been associated with sarcopenia, decreased grip strength and other impaired functionality measures in older adults (Visser et al 2003, Lee et al 2013, Post & Ilich 2013, Tieland et al 2013. Recent studies also showed that inverse relationship between vitamin D status and PTH concentrations is associated with compromised muscle mass and strength, as well as with diminished physical function (Lee et al 2013, Tieland et al 2013.…”
Section: Calcitriol As a Mediator For All Three Tissuesmentioning
confidence: 99%
See 2 more Smart Citations